MAKNA TRADISI PONAN BAGI PENGEMBANGAN PENDIDIKAN AKUNTANSI - Sudrajat Martadinata; Fadli Faturrahman (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2021)
The purpose of this research is to discover the significance of the Ponan tradition for the advancement of accounting education. The study was carried out in Poto Village, Moyo Hilir District, Sumbawa Regency. Purposive Sampling was used to identify the informants under the study. Ethnographic method was used as a data analysis tool. The Ponan tradition is divided into three meanings: gratitude, kinship, and fertility. The implication can be used as a guideline when developing an accounting education curriculum based on local wisdom.